2020
DOI: 10.3389/fimmu.2020.02037
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Response and Immunopathology of COVID-19

Abstract: Coronaviruses were first discovered in the 1960s and are named due to their crownlike shape. Sometimes, but not often, a coronavirus can infect both animals and humans. An acute respiratory disease, caused by a novel coronavirus (severe acute respiratory syndrome coronavirus-2 or SARS-CoV-2 previously known as 2019-nCoV) was identified as the cause of coronavirus disease 2019 (COVID-19) as it spread throughout China and subsequently across the globe. As of 14th July 2020, a total of 13.1 million confirmed case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
189
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 178 publications
(198 citation statements)
references
References 112 publications
(142 reference statements)
6
189
2
1
Order By: Relevance
“…Clinical observations quickly established that the main cause of the severe course of COVID-19 is not the lung damage itself, but hyperactive immune response leading to cytokine storm, systemic in ammation, and downstream acute respiratory distress syndrome (ARDS) 30 . It was shown that the virus has complex interaction with the innate and adaptive immunity and can directly infect the immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical observations quickly established that the main cause of the severe course of COVID-19 is not the lung damage itself, but hyperactive immune response leading to cytokine storm, systemic in ammation, and downstream acute respiratory distress syndrome (ARDS) 30 . It was shown that the virus has complex interaction with the innate and adaptive immunity and can directly infect the immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Lu et al, (2020) revealed that the viral "S" protein binding of SARS-CoV-2 is comparatively weaker than that of SARS-CoV. Mortaz et al, (2020) demonstrated that after viral adherence to the respiratory tract, ACE2 is released and both of the Inflammatory Nuclear Factor Kappa B (NF-KB) and the Signal Transducer and Activator of Transcription 3 (STAT3) are activated by the SARS-CoV-2 (IL-6 amplifier or IL-6 Amp), resulting in autoimmune and multiple inflammatory diseases. Usually, the Pattern recognition receptors (PRRs) identify the pathogenassociated molecular patterns (PAMPs) such as the viral RNA.…”
Section: Immunopathologymentioning
confidence: 95%
“…In addition, the T helper cells play important roles in producing the cytokines. The host immune response is usually suppressed by SARS-CoV-2 through elucidating apoptosis of the T cells, as suggested by Mortaz et al, (2020). According to Huang et al, (2020); Qin et al, (2020); Tan et al, (2020), the number of CD4 + , CD8 + , NK, B cells and the memory helper T cells (CD3 + , CD45, RO + ) were recorded to be significantly decreased in severe COVID-19 patients.…”
Section: Immunopathologymentioning
confidence: 98%
See 1 more Smart Citation
“…The adaptive immune response also comes into play. Helper CD4+, cytotoxic CD8+, and NK cells are activated and play a role in limiting the infection [ 47 ]. Cytotoxic CD8+ cells directly kill virus-infected cells.…”
Section: The Immune Response To Sars-cov-2mentioning
confidence: 99%